Sodium-ion battery negative electrode material heterostructure, construction method and performance prediction method

By constructing SiC/Nb1-xAxCO2 heterostructure and introducing Ge or Sn alloy elements, the structural collapse and safety problems caused by the large sodium atomic radius of the anode material of sodium ion batteries are solved, and the structural stability and electrochemical performance of the material are significantly improved.

CN119905185AActive Publication Date: 2025-04-29LANZHOU UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202510357749.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-29
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

Due to the large radius of sodium atoms, the volume changes greatly during charging and discharging, resulting in collapse of the material structure and reducing the lifespan; the low melting point of sodium is not directly used as the negative electrode, and it is easy to react with organic solvents to form dendrites, causing safety problems.

Method used

The SiC/Nb1-xAxCO2 heterostructure was constructed, and the material structure was optimized by introducing Ge or Sn alloy elements, the ion storage and transmission capacity was improved, the diffusion barrier was reduced, and performance prediction was performed through first-principles density functional theory simulation.

Benefits of technology

It significantly improves the structural stability and electrochemical performance of the negative electrode material of sodium ion battery, enhances the adsorption capacity of Na atoms, improves the conductivity and cyclic stability, extends the battery life, and reduces safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905185A_ABST
    Figure CN119905185A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery negative electrode material heterostructure, a construction method and a performance prediction method, and belongs to the technical field of electrochemical energy storage, Nb atoms are replaced by Ge or Sn to obtain Nb < 1-x > AxCO2, and then the Nb < 1-x > AxCO2 is compounded with 2D SiC to construct a SiC / Nb < 1-x > AxCO2 heterostructure, so that a sodium ion battery negative electrode material with improved electrochemical performance is obtained. The single-layer Nb2CO2 MXene provides good electronic conductivity and structural stability for the negative electrode material, and the introduction of SiC ensures excellent structural stability and high theoretical capacity; a heterostructure interface formed by SiC and Nb < 1-x > A < x > CO2 plays an important role in promoting electron conductivity and Na ion transfer. Due to the fact that Ge and Sn are close to C in electronegativity, the strength of A-C bonds formed between alloy elements and C is larger than that of Nb-C bonds, the stability of the heterostructure is enhanced, and the integrity of the electrode structure is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a heterogeneous structure of a negative electrode material for a sodium ion battery, a construction method and a performance prediction method. Background Art

[0002] In recent years, the search for clean, low-carbon, safe and efficient electricity storage methods has become a hot topic, and electrochemical energy storage has become an increasingly important research topic. Sodium is abundant in the earth's crust. The standard hydrogen electrode potential of the sodium electrode is -2.71V, and the redox potential is 0.3V higher than that of the lithium electrode. Therefore, the sodium electrode has a safer redox potential and stronger chemical stability, which makes sodium-ion batteries, or SIBs, stand out among many rechargeable metal-ion batteries. Although the experience of existing lithium-ion batteries, or LIBs, can play an important role in the development of SIBs. However, compared to Li + , Na + The larger ionic radius leads to Na + Slow diffusion reaction kinetics in electrode materials. Secondly, the mass of sodium is also larger than that of lithium, and it has a higher standard electrode potential, i.e. -2.71 V vs. -3.02 V, which is bound to reduce the energy density of SIBs. Electrode materials, including negative electrodes and cathodes, are the main factors that determine the reversible storage capacity, high energy density and long cycle life of batteries. Compared with positive electrode materials, the selection of negative electrode materials is the most difficult part to solve in SIBs. First, the atomic radius of sodium is relatively large, resulting in large volume changes during charge and discharge. After long cycles, the material structure will collapse and the life will be reduced. Secondly, sodium has a low melting point and cannot be used directly as a negative electrode. It is also easy to react with organic solvents and form dendrites during the cycle, causing safety problems.

[0003] Since sodium ions have a larger ionic radius than lithium ions, the ion diffusion rate is slow, and the volume expansion of the electrode material is also larger during the charge and discharge process, which causes the electrode rate performance and cycle stability to deteriorate. MXene has a hydrophilic surface and high metal conductivity, which shows good performance in energy storage, catalysis and many other fields. The layered structure and more metal surface active sites of MXene provide abundant channels for the storage and transportation of sodium ions. However, due to the limitations of preparation conditions, MXene will inevitably stack, reduce the specific surface area, and lead to a decrease in ion adsorption sites. At the same time, multilayer MXene is not stacked in an orderly manner, losing the advantages of the two-dimensional material itself.

[0004] As an advanced functional ceramic material, SiC has good thermal shock resistance, high temperature resistance, good chemical stability and high modulus, but its practical application is often limited by the brittleness of ceramic materials. Alloy-type negative electrode materials have high sodium storage capacity and relatively suitable working potential. Among the many new negative electrode materials, group IV alloy-based elements, including germanium and tin, can react with a large amount of sodium to form alloys. They have attracted much attention due to their high volumetric and mass capacity, low working potential and natural abundance. In sodium-ion batteries, Sn alloy materials can react with sodium to form alloys and store 3.75 mol of sodium ions, with a high theoretical specific capacity of about 847 mAh / g. In addition, Sn also has the advantages of non-toxicity, high abundance and low cost. Another element, Ge, has a faster lithium ion diffusion rate, good conductivity and a higher theoretical specific capacity, which is 369 mAh / g for SIBs. However, the practical application of germanium and tin alloy-based negative electrode materials is mainly limited by the large volume change, which leads to material pulverization or even detachment from the current collector, resulting in poor cycling ability and capacity decay. Summary of the invention

[0005] In view of the above problems, the present invention provides a heterogeneous structure of a negative electrode material for a sodium ion battery, a construction method and a performance prediction method, which effectively solves the technical defects that the volume change during charging and discharging is large due to the large radius of sodium atoms, and the material structure collapses after a long cycle, thereby reducing the lifespan; sodium has a low melting point and cannot be directly used as a negative electrode, and is easily reacted with organic solvents to form dendrites during the cycle, causing safety problems. At the same time, a structural model of a negative electrode material for a sodium ion battery with a suitable pore size is provided, which can realize ion storage and alleviate damage caused by ion transport.

[0006] The first object of the present invention is to provide a method for constructing a heterostructure of a negative electrode material for a sodium ion battery, comprising the following steps: Construct phase Nb 2 C and SiC structural model, the bulk Nb 2 C and SiC structure models were optimized and then 2D Nb 2 CO 2 Unit cell model and SiC unit cell model; based on the Nb 2 CO 2 The unit cell model and SiC unit cell model are used to construct a single layer Nb 2 CO 2 Supercell model and single-layer SiC supercell model.

[0007] Introducing alloying element A into single-layer Nb 2 CO 2 Supercell model, get Nb 1-x A x CO 2 Model.

[0008] The SiC supercell is placed on the Nb 2 CO 2 Supercell top, constructing SiC / Nb 2 CT x Heterostructure model; in the Nb 1-x A x CO 2 A single layer of SiC supercell is placed on top of the model. After structural optimization, SiC / Nb 1-x A x CO 2 Heterostructure model, the alloy element A is Ge or Sn, and X is 0.15-0.75.

[0009] As a preferred embodiment, when the alloy element A is Ge and X is 0.25, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.75 Ge 0.25 CO 2 , the lattice parameter is 6.31Å; when the alloy element A is Ge and X is 0.50, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.50 Ge 0.50 CO 2 , the lattice parameter is 6.15Å.

[0010] As a preferred embodiment, when the alloy element A is Sn and X is 0.25, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.75 Sn 0.25 CO 2 , the lattice parameter is 6.46Å; when the alloy element A is Sn and X is 0.50, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.50 Sn 0.50 CO 2 , the lattice parameter is 6.35Å.

[0011] As a preferred embodiment, the single layer Nb 2 CO 2The supercell model is a 2×2×1 supercell model with lattice parameters and angles of a=b=3.18Å, α=β=90° and γ=120° and Nb-C bond length of d Nb-C =2.16Å; the single-layer SiC supercell model is a 2×2×1 supercell model, with a lattice constant of a=b=3.10Å and a Si-C bond length of d Si-C =1.78Å.

[0012] As a preferred embodiment, when the alloy element A is Ge and X is 0.25, the Nb 1-x A x CO 2 Model Nb 0.75 Ge 0.25 CO 2 , the lattice constant is a=b=3.10Å, and the Nb-C bond length is d Nb-C = 2.15Å, Ge-C bond length is d Ge-C =2.13Å; when the alloy element A is Ge and X is 0.50, the Nb 1-x A x CO 2 Model Nb 0.50 Ge 0.50 CO 2 , the lattice constant is a=b=3.02Å, and the Nb-C bond length is d Nb-C = 2.15Å, Ge-C bond length is d Ge-C =2.13Å.

[0013] As a preferred embodiment, when the alloy element A is Sn and X is 0.25, the Nb 1-x A x CO 2 Model Nb 0.75 Sn 0.25 CO 2 , the lattice constant is a=b=3.15Å, and the Nb-C bond length is d Nb-C = 2.15Å, Sn-C bond length is d Sn-C =2.17Å; when the alloy element A is Sn and X is 0.50, the Nb 1-x A x CO 2 Model Nb 0.50 Sn 0.50 CO 2 , the lattice constant is a=b=3.12Å, and the Nb-C bond length is d Nb-C = 2.15Å, Sn-C bond length is d Sn-C =2.17Å.

[0014] The second object of the present invention is to provide a heterogeneous structure of a negative electrode material for a sodium ion battery constructed using the above-mentioned construction method.

[0015] The third object of the present invention is to provide a performance prediction method for the above-mentioned heterostructure of sodium ion battery negative electrode material, wherein the performance prediction includes energy stability prediction, thermodynamic stability prediction, sodium ion adsorption stability prediction on the heterostructure and conductivity prediction.

[0016] The performance prediction method comprises the following steps: For the SiC / Nb 1-x A x CO 2 The heterogeneous structure model was simulated by ab initio molecular dynamics to obtain the energy-time curve; the SiC / Nb 1-x A x CO 2 The formation energy and phonon spectrum of the heterostructure model are used to predict energy stability based on the energy-time variation curve, and the thermodynamic stability is predicted based on the formation energy and phonon spectrum.

[0017] In the SiC / Nb 1-x A x CO 2 In the heterostructure, SiC side and Nb 1-x A x CO 2 One side and the SiC / Nb 1-x A x CO 2 Na atoms were added to different typical sites between heterostructure layers to obtain a sodium atom adsorption model.

[0018] The adsorption energy of sodium atoms on the surface of negative electrode materials is calculated based on the sodium atom adsorption model, and the adsorption stability of sodium ions on heterogeneous structures is predicted.

[0019] By calculating SiC / Nb 1-x A x CO 2 The electronic properties of the heterostructure before and after the adsorption of sodium ions and the sodium ions in the SiC / Nb 1-x A x CO 2 Adsorption behavior, diffusion kinetics, open circuit voltage and theoretical specific capacity on heterostructures, and conductivity prediction.

[0020] As a preferred embodiment, the method for constructing the sodium atom adsorption model is specifically as follows: Select the C atom on one side of SiC, the Si atom, the top of the C atom in SiC, and the Na atom 2Å above the Si-C bond bridge to obtain the Na in SiC / Nb 1-x A x CO 2 Adsorption model on the SiC side of the heterostructure.

[0021] Select Nb 2 CO 2 / Nb 1-x A x CO 2 Na atoms were added to the C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and 2Å above the bridge of Nb-O / AC bonds on one side to obtain Na on SiC / Nb 1-x A x CO 2 Heterostructure Nb 2 CO 2 / Nb 1-x A x CO 2 Adsorption model on one side.

[0022] Select interlayer C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and add Na atoms 2Å above the bridge of Nb-O / AC bonds to obtain Na atoms in SiC / Nb 1-x A x CO 2 Adsorption model between heterostructure layers.

[0023] As a preferred implementation, the electronic performance data are electronic band structure, state density, differential charge density and electronic localization function.

[0024] As a preferred embodiment, the calculation is implemented based on the first principles in the CASTEP module, and the exchange-correlation functional is described by the GGA-PBE generalized gradient method.

[0025] As a preferred embodiment, when calculating electronic performance data, the plane wave cutoff energy is set to 450 eV, and a 4×4×1 K-point grid is used for Brillouin zone integration; during the calculation process, the atoms are fully relaxed, and the force and energy convergence criteria are set to 0.01 eVÅ respectively. -1 and 1×10 -5 eV.

[0026] As a preferred embodiment, in the calculation process of adsorption behavior, diffusion dynamics and theoretical specific capacity, the DFT-D3 method with Grimme correction is used to describe the long-range van der Waals interaction, and a vacuum layer greater than 15Å is set along the z direction to avoid interlayer interaction.

[0027] As a preferred embodiment, when performing ab initio molecular dynamics simulation, the Nosé-Hoover method is used to control the temperature and NVT ensemble conditions to perform ab initio molecular dynamics simulation, the temperature is set to 300K, the simulation duration is 3000fs, and the time step is 1fs.

[0028] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a heterogeneous structure of anode materials for sodium ion batteries, a construction method and a performance prediction method, and uses a first-principle density functional theory simulation method to perform SiC / Nb 1-x A x CO 2 Heterostructure model construction, Nb is obtained by replacing Nb atoms with Ge or Sn alloy elements 1-x A x CO 2 , and then composited with 2D SiC material to construct a SiC / Nb 1-x A x CO 2 Heterogeneous structure, thus obtaining a sodium ion battery negative electrode material with improved electrochemical performance. 2 CO 2 The good mechanical properties and high metallic properties of MXene itself provide good electronic conductivity and structural stability for the negative electrode material. The introduction of ceramic semiconductor material SiC, with its inherent high hardness and strength, further ensures excellent structural stability and high theoretical capacity, while improving Nb 1-x A x CO 2 Aggregation of MXene nanosheets; The metallic behavior of the constructed heterostructure improves the electronic conductivity of the negative electrode material during battery operation; 1-x A x CO 2 The heterostructure interface formed plays an important role in promoting electronic conductivity and Na ion transfer. In addition, due to the electronegativity of the alloying elements Ge and Sn and C, the AC bond chemical bond strength formed between the alloying elements and C is stronger than the Nb-C bond, thereby enhancing the stability of the material structure itself, which is beneficial to maintaining the integrity of the electrode structure.

[0029] The SiC / Nb 1-x Ax CO 2 The heterostructure has a significantly enhanced Na atom adsorption capacity. In addition, due to the synergistic promotion of alloying elements, the electronic conductivity is accelerated, further improving its applicability as an electrode; 1-x A x CO 2 Between the heterostructure layers, Na exhibits a reduced diffusion barrier, which ensures its high ion mobility; compared with the intrinsic SiC / Nb 2 CO 2 Compared with heterostructure, SiC / Nb 1-x A x CO 2 With significantly improved theoretical capacity; Na atom-loaded SiC / Nb 1-x A x CO 2 The heterostructure exhibits enhanced conductivity, and the heterostructure system with Na adsorption has good energy stability. At the same time, based on the first-principle calculation method, the present invention reveals the influence of alloy elements on the electrochemical behavior of negative electrode materials from a microscopic level, and provides ideas for the rapid and effective prediction and design of new electrode materials with stable structure and improved performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Nb is provided in the embodiment of the present invention 2 CO 2 Single-layer model.

[0031] Figure 2 This is a SiC single layer model provided by an embodiment of the present invention.

[0032] Figure 3 Nb is provided in the embodiment of the present invention 1-x A x CO 2 Single-layer model.

[0033] Figure 4 The intrinsic SiC / Nb 2 CO 2 Heterostructure model.

[0034] Figure 5 The SiC / Nb ratio at different concentrations provided by the embodiment of the present invention is 1-x A x CO 2 Heterojunction model.

[0035] Figure 6 The intrinsic SiC / Nb 2 CO 2 and SiC / Nb1-x A x CO 2 Heterostructure AIMD simulation, wherein Figure a is comparative example 1, Figure b is example 1, Figure c is example 2, Figure d is example 3, and Figure e is example 4.

[0036] Figure 7 is a Na adsorption model at different sites provided by an embodiment of the present invention, wherein Figure a is a Na adsorption model at different sites on SiC / Nb 1-x A x CO 2 Adsorption model of the heterogeneous structure SiC side, Figure b shows Na on SiC / Nb 1-x A x CO 2 Heterostructure Nb 2 CO 2 / Nb 1-x A x CO 2 The adsorption model on one side, Figure c is Na on SiC / Nb 1-x A x CO 2 Adsorption model between heterostructure layers.

[0037] Figure 8 SiC / Nb provided in Example 1 of the present invention 0.75 Ge 0.25 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure, where a1 to a3 are the SiC / Nb 0.75 Ge 0.25 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0038] Fig. 9 The SiC / Nb provided in Example 2 of the present invention 0.50 Ge 0.50 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure, wherein Figure b1 to Figure b3 are respectively the SiC / Nb 0.50 Ge 0.50 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0039] Fig.10 The SiC / Nb provided in Example 3 of the present invention 0.75 Sn 0.25 CO 2The electronic band structure, state density and differential charge density diagram of the heterostructure, where Figure c1 to Figure c3 are the SiC / Nb 0.75 Sn 0.25 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0040] Fig.11 The SiC / Nb provided in Example 4 of the present invention 0.50 Sn 0.50 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure, wherein the d1 diagram to the d3 diagram are respectively the SiC / Nb 0.50 Sn 0.50 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0041] Fig.12 The SiC / Nb provided in Example 1 of the present invention 0.75 Ge 0.25 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure after sodiumization, wherein a1 to a3 are the SiC / Nb after sodiumization in Example 1. 0.75 Ge 0.25 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0042] Fig.13 The SiC / Nb provided in Example 2 of the present invention 0.50 Ge 0.50 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure after sodiumization, wherein Figure b1 to Figure b3 are respectively the SiC / Nb after sodiumization in Example 2 0.50 Ge 0.50 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0043] Fig.14 The SiC / Nb provided in Example 3 of the present invention 0.75 Sn 0.25 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure after sodiumization, wherein Figure c1 to Figure c3 are respectively the SiC / Nb after sodiumization in Example 3 0.75 Sn 0.25 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0044] Fig.15 The SiC / Nb provided in Example 4 of the present invention 0.50 Sn 0.50 CO 2 The electronic band structure, state density and differential charge density diagram of the heterostructure after sodiumization, wherein d1 to d3 are the SiC / Nb after sodiumization in Example 4, respectively. 0.50 Sn 0.50 CO 2 Electronic band structure, density of states, and differential charge density diagram of the heterostructure.

[0045] Fig.16 The single Na atom provided by the embodiment of the present invention is intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 Diffusion barriers between heterogeneous structure layers, wherein Figure A is Comparative Example 1, Figure B is Example 1, Figure C is Example 3, and Figure D is Example 4. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0047] In view of the following technical problems mentioned in the background technology of the present invention: First, the atomic radius of sodium is too large, resulting in a large volume change during charge and discharge, which will cause the material structure to collapse after a long cycle and reduce the lifespan; secondly, sodium has a low melting point and cannot be directly used as a negative electrode, and it is easy to react with organic solvents, and dendrites will be formed during the cycle, causing safety problems. Second, since sodium ions have a larger ionic radius than lithium ions, the ion diffusion rate is slow, and the volume expansion of the electrode material during the charge and discharge process is also larger, which causes the electrode rate performance and cycle stability to deteriorate. Although MXene has a hydrophilic surface, high metal conductivity, a layered structure and more metal surface active sites, it provides abundant channels for the storage and transportation of sodium ions, but MXene will inevitably stack, reduce the specific surface area, and reduce the ion adsorption sites, and multilayer MXene is not stacked in an orderly manner, so it loses the advantages of the two-dimensional material itself. Third, although SiC has good thermal shock resistance, high temperature resistance, good chemical stability and high modulus, it is relatively brittle. Fourth, alloy-type negative electrode materials have a high sodium storage capacity and a relatively suitable working potential. Among the many new negative electrode materials, Group IV alloy-based elements, including germanium and tin, can react with a large amount of sodium to form an alloy. They have attracted much attention due to their high volume and mass capacity, low working potential and natural abundance. However, in actual applications, the volume change of germanium and tin alloy-based negative electrode materials is too large, resulting in material pulverization and even falling off from the current collector, resulting in poor cycle capacity and capacity decay.

[0048] The technical solution of the present invention is described in detail below.

[0049] The present invention first provides a method for constructing a heterogeneous structure of a negative electrode material for a sodium ion battery, comprising the following steps: Material Studio software was used to construct the body phase Nb 2 C and SiC structure models, the bulk structure was optimized based on the CASTEP module, and the 2D Nb 2 CO 2 Unit cell model and SiC unit cell model; construct a single layer Nb based on the unit cell model 2 CO 2 Supercell model and single-layer SiC supercell model.

[0050] Introducing alloying element A into single-layer Nb 2 CO 2 Supercell, get Nb 1-x A x CO 2 Model.

[0051] For the intrinsic SiC / Nb 2 CO 2 and Nb1-x A x CO 2 The heterostructure model sets convergence parameters in the CASTEP module and performs complete relaxation to obtain the lowest energy stable configuration and corresponding characteristic parameters, including changes in lattice parameters, bond lengths, and bond angles.

[0052] The SiC supercell is placed on the Nb 2 CO 2 At the top of the supercell, the Build layer function is used to build SiC / Nb 2 CT x Heterostructure model; in the Nb 1-x A x CO 2 A single layer of SiC supercell is placed on the top of the model, and after structural optimization using the CASTEP module, the SiC / Nb 1-x A x CO 2 Heterostructure model, the alloy element A is Ge or Sn, and X is 0.25 or 0.50.

[0053] It should be noted that when the alloy element A is Ge and X is 0.25, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.75 Ge 0.25 CO 2 , the lattice parameter is 6.31Å; when the alloy element A is Ge and X is 0.50, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.50 Ge 0.50 CO 2 , the lattice parameter is 6.15Å. When the alloy element A is Sn and X is 0.25, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.75 Sn 0.25 CO 2 , the lattice parameter is 6.46Å; when the alloy element A is Sn and X is 0.50, the SiC / Nb 1-x A x CO 2 Heterostructure model is SiC / Nb 0.50 Sn 0.50 CO 2 , the lattice parameter is 6.35Å.

[0054] It should be noted that the single layer Nb 2 CO 2 The supercell model is a 2×2×1 supercell model with lattice parameters and angles of a=b=3.18Å, α=β=90° and γ=120° and Nb-C bond length of d Nb-C =2.16Å; the single-layer SiC supercell model is a 2×2×1 supercell model, with a lattice constant of a=b=3.10Å and a Si-C bond length of d Si-C =1.78Å.

[0055] It should be emphasized that when the alloy element A is Ge and X is 0.25, the Nb 1-x A x CO 2 Model Nb 0.75 Ge 0.25 CO 2 , the lattice constant is a=b=3.10Å, and the Nb-C bond length is d Nb-C = 2.15Å, Ge-C bond length is d Ge-C =2.13Å; when the alloy element A is Ge and X is 0.50, the Nb 1-x A x CO 2 Model Nb 0.50 Ge 0.50 CO 2 , the lattice constant is a=b=3.02Å, and the Nb-C bond length is d Nb-C = 2.15Å, Ge-C bond length is d Ge-C =2.13Å.

[0056] When the alloy element A is Sn and X is 0.25, the Nb 1-x A x CO 2 Model Nb 0.75 Sn 0.25 CO 2 , the lattice constant is a=b=3.15Å, and the Nb-C bond length is d Nb-C = 2.15Å, Sn-C bond length is d Sn-C =2.17Å; when the alloy element A is Sn and X is 0.50, the Nb 1-x A x CO 2 Model Nb 0.50 Sn 0.50 CO 2 , the lattice constant is a=b=3.12Å, and the Nb-C bond length is d Nb-C = 2.15Å, Sn-C bond length is d Sn-C=2.17Å.

[0057] The second object of the present invention is to provide a heterogeneous structure of a negative electrode material for a sodium ion battery constructed using the above-mentioned construction method.

[0058] After optimization, intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 The structural stability of the heterogeneous structure is calculated based on the intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 The total energy after complete relaxation of the heterostructure is calculated as the intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 The phonon spectra, formation energy, i.e., Ef, and ab initio molecular dynamics simulation, i.e., AIMD, of the heterostructure models confirm the energy stability and thermodynamic stability of these heterostructure systems.

[0059] After the above confirmation of the stability of the heterostructure, the intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 The electronic properties of heterostructures, including electronic band structure, state density, differential charge density, work function, electron localization function and Mulliken population analysis, are used to obtain the influence of alloy element type and concentration on conductivity, electronic structure and interatomic bonding.

[0060] The third object of the present invention is to provide a performance prediction method for the above-mentioned heterostructure of sodium ion battery negative electrode material, wherein the performance prediction includes energy stability prediction, thermodynamic stability prediction, sodium ion adsorption stability prediction on the heterostructure and conductivity prediction.

[0061] The performance prediction method comprises the following steps: For the SiC / Nb 1-x A x CO 2 The heterogeneous structure model was simulated by ab initio molecular dynamics to obtain the energy-time curve; the SiC / Nb 1-x A x CO 2The formation energy and phonon spectrum of the heterostructure model are used to predict energy stability based on the energy-time variation curve, and the thermodynamic stability is predicted based on the formation energy and phonon spectrum.

[0062] In the SiC / Nb 1-x A x CO 2 In the heterostructure, SiC side and Nb 1-x A x CO 2 One side and the SiC / Nb 1-x A x CO 2 Na atoms were added to different typical sites between heterostructure layers to obtain a sodium atom adsorption model.

[0063] Specifically, the method for constructing the sodium atom adsorption model is as follows: Select the C atom on one side of SiC, the Si atom, the top of the C atom in SiC, and the Na atom 2Å above the Si-C bond bridge to obtain the Na in SiC / Nb 1-x A x CO 2 Adsorption model on the SiC side of the heterostructure.

[0064] Select Nb 2 CO 2 / Nb 1-x A x CO 2 Na atoms were added to the C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and 2Å above the bridge of Nb-O / AC bonds on one side to obtain Na on SiC / Nb 1-x A x CO 2 Heterostructure Nb 2 CO 2 / Nb 1-x A x CO 2 Adsorption model on one side.

[0065] Select interlayer C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and add Na atoms 2Å above the bridge of Nb-O / AC bonds to obtain Na atoms in SiC / Nb 1-x A x CO 2 Adsorption model between heterostructure layers.

[0066] The adsorption structure obtained above is completely relaxed, and the adsorption energy of the stable configuration is calculated, that is, E adand characteristic parameters; compare the adsorption energies of various heterostructures and screen out the heterostructure adsorption model with the most stable adsorption energy in each type of heterostructure.

[0067] Based on the above most stable heterostructure adsorption model, the obtained electronic band structure, state density, differential charge density, work function, electron localization function and Mulliken population analysis were analyzed to reveal the microscopic mechanism of the change of electronic properties of the system before and after sodium adsorption.

[0068] The adsorption energy of sodium atoms on the surface of the negative electrode material is calculated to predict the adsorption stability of sodium ions on the heterostructure. Based on the above adsorption energy results, the diffusion paths of Na atoms are set on both sides and between layers of each heterostructure. Reaction Preview is used to select the most stable adsorption configuration and the adjacent most stable adsorption configuration from the stable adsorption model as the starting state and final state of the migration, and use them as reactants and products, respectively.

[0069] Based on the lowest energy configurations of the initial and final states, the CI-NEB method was used to calculate the transition state, analyze the obtained migration barriers and diffusion rates, obtain the optimal reaction path, and establish the mechanism of the influence of alloy elements on the diffusion dynamics of heterostructures.

[0070] By calculating SiC / Nb 1-x A x CO 2 The electronic properties of the heterostructure before and after the adsorption of sodium ions and the sodium ions in the SiC / Nb 1-x A x CO 2 Adsorption behavior, diffusion kinetics, open circuit voltage and theoretical specific capacity on heterostructures are used to predict conductivity, power density and cycle performance.

[0071] According to the adsorption energy of sodium atoms on the surface of the negative electrode material, the first sodium atomic layer is added layer by layer at the most stable site, and the corresponding layer order adsorption energy, i.e., E layer-n ; Then add a second sodium atomic layer at the secondary stable site, and obtain the layer-by-layer adsorption energy in sequence until the value is positive or close to positive, which is the maximum number of sodium atomic layers that can be accommodated.

[0072] The structural stability and thermal stability of each heterostructure type with different Na atomic concentration loading were simulated. Phonon dispersion curve calculations were performed in CASTEP module and thermal stability simulations were implemented in first-principles molecular dynamics in DMol3 module.

[0073] To accurately determine the maximum adsorption concentration of Na atoms, add host atoms to the substrate one by one and simultaneously calculate the corresponding sequential adsorption energy, i.e., E sae, until its value becomes positive to accurately obtain the maximum Na atom storage concentration for each heterostructure.

[0074] With the embedding of sodium atoms, the formation energy of different configurations of negative electrode materials loaded with the same concentration of Na atoms is calculated, and the convex hull diagram is drawn to further obtain the energy-stable intermediate phase in the Na loading process.

[0075] Based on the above convex hull diagram, the open circuit voltage corresponding to the stable middle is obtained, and the corresponding theoretical specific capacity at the maximum Na atomic concentration is calculated. The changes in the open circuit voltage and theoretical specific capacity of the system before and after the introduction of alloy elements are analyzed.

[0076] As a preferred implementation, the electronic performance data are electronic band structure, state density, differential charge density and electronic localization function.

[0077] As a preferred embodiment, the calculation is implemented based on the first principles in the CASTEP module, and the exchange-correlation functional is described by the GGA-PBE generalized gradient method.

[0078] In the present invention, when calculating the electronic performance data, the plane wave cutoff energy is set to 450 eV, and a 4×4×1 K-point grid is used for Brillouin zone integration; during the calculation process, the atoms are fully relaxed, and the force and energy convergence criteria are set to 0.01 eVÅ respectively. -1 and 1×10 -5 eV.

[0079] It should be emphasized that in the calculation of adsorption behavior, diffusion kinetics and theoretical specific capacity, the DFT-D3 method with Grimme correction was used to describe the long-range van der Waals interaction, and a vacuum layer larger than 15 Å was set along the z direction to avoid interlayer interactions.

[0080] It should be noted that when performing ab initio molecular dynamics simulations, the Nosé-Hoover method was used to control the temperature and NVT ensemble conditions, with the temperature set to 300 K, the simulation duration to 3000 fs, and the time step to 1 fs.

[0081] The present invention is specifically described below by means of the following examples and comparative examples.

[0082] Example 1 A SiC / Nb 0.75 Ge 0.25 CO 2 The method for constructing a heterostructure comprises the following steps: Material Studio software was used to construct the body phase Nb 2C and SiC structure models, the bulk structure was optimized based on the CASTEP module, and the 2D Nb 2 CO 2 Unit cell model and SiC unit cell model; construct a single layer Nb based on the unit cell model 2 CO 2 Supercell model and single-layer SiC supercell model.

[0083] Introducing the alloy element Ge into the monolayer Nb 2 CO 2 Supercell, get Nb 0.75 Ge 0.25 CO 2 Model.

[0084] For the Nb constructed above 0.75 Ge 0.25 CO 2 The calculation parameters of the heterostructure model were set in the CASTEP module. The plane wave cutoff energy was set to 450 eV, and a 4×4×1 K-point grid was used for Brillouin zone integration. During the calculation, the atoms were fully relaxed, and the force and energy convergence criteria were set to 0.01 eVÅ. -1 and 1×10 -5 eV, complete relaxation is performed to obtain the lowest energy stable configuration and corresponding characteristic parameters, including changes in lattice parameters, bond lengths and bond angles.

[0085] The SiC supercell is placed on the Nb 2 CO 2 At the top of the supercell, the Build layer function is used to build SiC / Nb 2 CT 25 Heterostructure model; in the Nb 0.75 Ge 0.25 CO 2 A single layer of SiC supercell is placed on the top of the model, and after structural optimization using the CASTEP module, the SiC / Nb 0.75 Ge 0.25 CO 2 Heterostructure model.

[0086] Example 2 A SiC / Nb 0.50 Ge 0.50 CO 2 The method for constructing a heterostructure comprises the following steps: Material Studio software was used to construct the body phase Nb 2 C and SiC structure models, the bulk structure was optimized based on the CASTEP module, and the 2D Nb 2CO 2 Unit cell model and SiC unit cell model; construct a single layer Nb based on the unit cell model 2 CO 2 Supercell model and single-layer SiC supercell model.

[0087] Introducing the alloy element Ge into the monolayer Nb 2 CO 2 Supercell, get Nb 0.50 Ge 0.50 CO 2 Model.

[0088] For the Nb constructed above 0.50 Ge 0.50 CO 2 The calculation parameters of the heterostructure model were set in the CASTEP module. The plane wave cutoff energy was set to 450 eV, and a 4×4×1 K-point grid was used for Brillouin zone integration. During the calculation, the atoms were fully relaxed, and the force and energy convergence criteria were set to 0.01 eVÅ. -1 and 1×10 -5 eV, complete relaxation is performed to obtain the lowest energy stable configuration and corresponding characteristic parameters, including changes in lattice parameters, bond lengths and bond angles.

[0089] The SiC supercell is placed on the Nb 2 CO 2 At the top of the supercell, the Build layer function is used to build SiC / Nb 2 CT 50 Heterostructure model; in the Nb 0.50 Ge 0.50 CO 2 A single layer of SiC supercell is placed on the top of the model, and after structural optimization using the CASTEP module, the SiC / Nb 0.50 Ge 0.50 CO 2 Heterostructure model.

[0090] Example 3 A SiC / Nb 0.75 Sn 0.25 CO 2 The method for constructing a heterostructure comprises the following steps: Material Studio software was used to construct the body phase Nb 2 C and SiC structure models, the bulk structure was optimized based on the CASTEP module, and the 2D Nb 2 CO 2 Unit cell model and SiC unit cell model; construct a single layer Nb based on the unit cell model 2 CO2 Supercell model and single-layer SiC supercell model.

[0091] Introducing the alloy element Sn into the single-layer Nb 2 CO 2 Supercell, get Nb 0.75 Sn 0.25 CO 2 Model.

[0092] For the Nb constructed above 0.75 Sn 0.25 CO 2 The calculation parameters of the heterostructure model were set in the CASTEP module. The plane wave cutoff energy was set to 450 eV, and a 4×4×1 K-point grid was used for Brillouin zone integration. During the calculation, the atoms were fully relaxed, and the force and energy convergence criteria were set to 0.01 eVÅ. -1 and 1×10 -5 eV, complete relaxation is performed to obtain the lowest energy stable configuration and corresponding characteristic parameters, including changes in lattice parameters, bond lengths and bond angles.

[0093] The SiC supercell is placed on the Nb 2 CO 2 At the top of the supercell, the Build layer function is used to build SiC / Nb 2 CT 25 Heterostructure model; in the Nb 0.75 Sn 0.25 CO 2 A single layer of SiC supercell is placed on the top of the model, and after structural optimization using the CASTEP module, the SiC / Nb 0.75 Sn 0.25 CO 2 Heterostructure model.

[0094] Example 4 A SiC / Nb 0.50 Sn 0.50 CO 2 The method for constructing a heterostructure comprises the following steps: Material Studio software was used to construct the body phase Nb 2 C and SiC structure models, the bulk structure was optimized based on the CASTEP module, and the 2D Nb 2 CO 2 Unit cell model and SiC unit cell model; construct a single layer Nb based on the unit cell model 2 CO 2 Supercell model and single-layer SiC supercell model.

[0095] Introducing the alloy element Sn into the single-layer Nb 2 CO 2 Supercell, get Nb 0.50 Sn 0.50 CO 2 Model.

[0096] For the Nb constructed above 0.50 Sn 0.50 CO 2 The calculation parameters of the heterostructure model were set in the CASTEP module. The plane wave cutoff energy was set to 450 eV, and a 4×4×1 K-point grid was used for Brillouin zone integration. During the calculation, the atoms were fully relaxed, and the force and energy convergence criteria were set to 0.01 eVÅ. -1 and 1×10 -5 eV, complete relaxation is performed to obtain the lowest energy stable configuration and corresponding characteristic parameters, including changes in lattice parameters, bond lengths and bond angles.

[0097] The SiC supercell is placed on the Nb 2 CO 2 At the top of the supercell, the Build layer function is used to build SiC / Nb 2 CT 50 Heterostructure model; in the Nb 0.50 Sn 0.50 CO 2 A single layer of SiC supercell is placed on the top of the model, and after structural optimization using the CASTEP module, the SiC / Nb 0.50 Sn 0.50 CO 2 Heterostructure model.

[0098] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows: Comparative Example 1 A SiC / Nb 2 CO 2 The method for constructing a heterostructure comprises the following steps: Material Studio software was used to construct the body phase Nb 2 C and SiC structure models, the bulk structure was optimized based on the CASTEP module, and the 2D Nb 2 CO 2 Unit cell model and SiC unit cell model; construct a single layer Nb based on the unit cell model 2 CO 2 Supercell model and single-layer SiC supercell model.

[0099] For the above constructed single-layer Nb 2 CO2 The supercell model sets the calculation parameters in the CASTEP module. The plane wave cutoff energy is set to 450 eV, and a 4×4×1 K-point grid is used for Brillouin zone integration. During the calculation, the atoms are fully relaxed, and the force and energy convergence criteria are set to 0.01 eVÅ. -1 and 1×10 -5 eV, complete relaxation is performed to obtain the lowest energy stable configuration and corresponding characteristic parameters, including changes in lattice parameters, bond lengths and bond angles.

[0100] The SiC supercell is placed on the Nb 2 CO 2 At the top of the supercell, the Build layer function is used to build SiC / Nb 2 CO 2 Heterogeneous structure model, after structural optimization through CASTEP module, SiC / Nb 2 CO 2 Heterostructure model.

[0101] The parameters and performances of the heterogeneous structure models constructed in the above-mentioned Examples 1 to 4 and Comparative Example 1 were tested, and the results are as follows.

[0102] Example 5 A sodium ion battery negative electrode material SiC / Nb 0.75 Ge 0.25 CO 2 The performance prediction method of the heterostructure comprises the following steps: For the SiC / Nb 0.75 Ge 0.25 CO 2 The heterogeneous structure model was subjected to ab initio molecular dynamics simulation to obtain the energy-time variation curve, such as Figure 6 Figure b in Figure 2; Calculate the SiC / Nb 1-x A x CO 2 The formation energy and phonon spectrum of the heterostructure model are used to predict energy stability based on the energy-time variation curve, and the thermodynamic stability is predicted based on the formation energy and phonon spectrum.

[0103] SiC / Nb 0.75 Ge 0.25 CO 2 The formation energies of the heterostructures are -2.13 eV, SiC / Nb 0.75 Ge 0.25 CO 2 The formation energy of heterostructure is negative, indicating that the system is a spontaneous exothermic reaction.

[0104] from Figure 6As can be seen in Figure b, after 3000 fs complete relaxation at room temperature, SiC / Nb 0.75 Ge 0.25 CO 2 The heterostructure undergoes only minor changes and the energy fluctuations are small, indicating that SiC / Nb 0.75 Ge 0.25 CO 2 The heterostructure model is thermodynamically stable.

[0105] In the SiC / Nb 0.75 Ge 0.25 CO 2 In the heterostructure, SiC side and Nb 0.75 Ge 0.25 CO 2 One side and the SiC / Nb 0.75 Ge 0.25 CO 2 Na atoms are added to different typical sites between heterostructure layers to obtain the sodium atom adsorption model, which is as follows: Select the C atom on one side of SiC, the Si atom, the top of the C atom in SiC, and the Na atom 2Å above the Si-C bond bridge to obtain the Na in SiC / Nb 0.75 Ge 0.25 CO 2 Adsorption model on the SiC side of the heterostructure.

[0106] Select Nb 0.75 Ge 0.25 CO 2 Na atoms were added to the C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and 2Å above the bridge of Nb-O / AC bonds on one side to obtain Na on SiC / Nb 0.75 Ge 0.25 CO 2 Heterostructure Nb 0.75 Ge 0.25 CO 2 Adsorption model on one side.

[0107] Select interlayer C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and add Na atoms 2Å above the bridge of Nb-O / AC bonds to obtain Na atoms in SiC / Nb 0.75 Ge 0.25 CO 2 Adsorption model between heterostructure layers.

[0108] According to the above sodium atom adsorption model at different sites, the adsorption energy E on the surface of the negative electrode material when sodium atoms are adsorbed at different sites is calculated. adand the vertical distance H from the Na atom to the substrate, as shown in Table 2, thus predicting the adsorption stability of sodium ions on the heterostructure. As shown in Table 2, the adsorption energies of all stable adsorption configurations of Na atoms are negative, indicating that Na atoms are stably adsorbed at all sites. 0.75 Ge 0.25 CO 2 The adsorption energy of the top carbon atom on one side of the heterostructure SiC is higher than that on the pure SiC / Nb 2 CO 2 The adsorption energies in the heterostructures are more negative, indicating that Na atoms prefer to occupy these sites.

[0109] By calculating SiC / Nb 0.75 Ge 0.25 CO 2 The electronic properties of the heterostructure before and after the adsorption of sodium ions and the sodium ions in the SiC / Nb 0.75 Ge 0.25 CO 2 Adsorption behavior, diffusion kinetics, open circuit voltage and theoretical specific capacity on heterostructures, and conductivity prediction.

[0110] Screening out SiC / Nb 0.75 Ge 0.25 CO 2 The configuration with the lowest heterostructure formation energy is calculated, and the electronic band structure, state density, differential charge density and Mulliken population analysis related electronic properties are analyzed, such as Figure 8~Figure 15 According to the electronic band structure and state density before and after Na adsorption, it can be seen that the Na-treated SiC / Nb 0.75 Ge 0.25 CO 2 The metallic nature of the heterostructure is beneficial to improving the conductivity of the electrode. The differential charge density of the Na adsorbed heterostructure is as follows: Fig.16 As shown in the figure, a large amount of electrons gather on the SiC side, while electrons are lost around the Na atoms, indicating the transfer of electrons from the Na atoms to the substrate. At the same time, the formation of electron density between the Na atoms and the substrate indicates that the strong chemical interaction between the Na atoms and the substrate is dominant. Mulliken population analysis further illustrates the above results. 0.75 Ge 0.25 CO 2 The heterostructure transfer is 0.809e, 0.862e, 0.839e and 0.867e. The electron localization function calculation analysis shows that there is a significant electron density between Ge-C, indicating that the interaction is covalent. By analyzing the electron energy band and state density, compared with the intrinsic SiC / Nb 2 CO 2The heterostructure significantly increases the electronic state at the Fermi level by introducing alloy elements. The heterostructure shows significantly improved conductivity, and as Na atoms are continuously embedded in the heterostructure, the metallic properties are still maintained. Thanks to the excellent theoretical capacity of the alloy element Ge and its small molar mass, SiC / Nb 0.75 Ge 0.25 CO 2 The heterostructure has significantly improved Na storage capacity compared with the pristine heterostructure.

[0111] Example 6 The SiC / Nb 0.75 Ge 0.25 CO 2 Heterostructure replaced with SiC / Nb 0.50 Ge 0.50 CO 2 Heterogeneous structure.

[0112] Example 7 The SiC / Nb 0.75 Ge 0.25 CO 2 Heterostructure replaced with SiC / Nb 0.75 Sn 0.25 CO 2 Heterogeneous structure.

[0113] Example 8 The SiC / Nb 0.75 Ge 0.25 CO 2 Heterostructure replaced with SiC / Nb 0.50 Sn 0.50 CO 2 Heterogeneous structure.

[0114] The detection data of each heterostructure of the above-mentioned Examples 6 to 8 are shown in Tables 1 and 2 below.

[0115] The model was built using Material Studio software and Nb was obtained by literature review. 2 AlC belongs to the hexagonal system with a space group of P63 / mmc. Then Nb is obtained from the crystal structure database Materials Project. 2 C precursor parent phase Nb 2 AlC, the bulk crystal structure is geometrically optimized to obtain a stable configuration. The unit cell Nb 2 C MXene monolayer, and then use Supercell to obtain a 2×2×1 supercell Nb 2 CO 2 MXene monolayer, such as Figure 1 By setting reasonable parameters in the CASTEP module, the BFGS algorithm is used to completely relax the supercell monolayer to obtain a stable structural model, and then the relevant characteristic parameters are calculated, where the lattice parameters and angles are a=b=3.18 Å, α=β=90° and γ=120°, and the Nb-C bond length is d Nb-C =2.16 Å.

[0116] Single-layer SiC model construction and optimization: The bulk structure is obtained in the MS structure library and the geometry is optimized. Based on the stable crystal structure model, the single-layer SiC unit cell structure is obtained by sectioning and a 2×2×1 supercell model is obtained, such as Figure 2 According to the characteristics of SiC, the calculation parameters are reasonably set to optimize its structure to obtain a single-layer SiC supercell model with the lowest total energy, and then the relevant characteristic parameters are calculated. The lattice constant is a=b=3.10 Å, and the Si-C bond length is d Si-C =1.78 Å.

[0117] Single layer Nb 1-x A x CO 2 Model building and optimization: Constructing Nb with different contents of Ge and Sn 1-x A x CO 2 The 2×2×1 supercell model Nb 0.75 Ge 0.25 CO 2 , Nb 0.50 Ge 0.50 CO 2 , Nb 0.75 Sn 0.25 CO 2 and Nb 0.50 Ge 0.50 CO 2 , use CASTEP to set the structural optimization parameters and perform geometry optimization to obtain a stable single layer of heterogeneous structure, such as Figure 3 The results of the lattice constants and bond lengths of each single layer are shown in Table 1.

[0118] Table 1 Nb of the present invention 1-x A x CO 2 Lattice constant and bond length of a single layer Intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x Ax CO 2 Heterogeneous structure model construction and optimization: Establishing intrinsic SiC / Nb 2 CO 2 and SiC / Nb with different alloying elements and contents 1-x A x CO 2 Heterojunction model, SiC / Nb 0.75 Ge 0.25 CO 2 、SiC / Nb 0.50 Ge 0.50 CO 2 、SiC / Nb 0.75 Sn 0.25 CO 2 、SiC / Nb 0.50 Sn 0.50 CO 2 ,like Figure 5 and Figure 6 As shown, the stable configuration of each heterostructure was obtained based on the first-principles optimization, and the influence of the type and content of alloy elements on the lattice parameters of the heterostructure was analyzed. The lattice parameters of each heterostructure are 6.31 Å, 6.15 Å, 6.46 Å and 6.35 Å, respectively.

[0119] Intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 Heterostructure Stability: The energy stability and thermodynamic stability of the optimized heterostructure model are calculated to obtain the formation energy of each heterostructure and the energy-time variation curve in the AIMD simulation, such as Figure 6 As shown. Among them, the formation energy of heterostructures with different alloy element types and concentrations are -6.26 eV, -2.13 eV, -2.06 eV, -2.91 eV, and -2.79 eV, respectively. The formation energy of each heterostructure is negative, indicating that the system is a spontaneous exothermic reaction. The corresponding formation energy formula is:

[0120] ; in, is the total energy of the heterostructure, and are the total energies of the two monolayers constituting the heterostructure.

[0121] From the energy-time curves in the AIMD simulation, it can be seen that after 3000 fs complete relaxation at room temperature, each heterostructure undergoes only a slight change and the energy fluctuation is very small, which means that the above model considered is thermodynamically stable.

[0122] Sodium atoms in intrinsic and SiC / Nb 1-x A x CO 2 Study on adsorption behavior on heterogeneous structures Sodium ion adsorption model construction: Based on the optimized intrinsic SiC / Nb 2 CO 2 and SiC / Nb 1-x A x CO 2 The heterostructure is used as a substrate to construct the adsorption structure of a single Na atom on both sides of the heterostructure and at typical sites between the layers, such as Figure 7 As shown. For the SiC side, the C atoms T C 、Si atom T Si , the top T of C atoms in SiC C(SiC) and Si-C bond bridge B Si-C Adding Na atoms at a distance of 2Å above gives Na in SiC / Nb 1-x A x CO 2 Adsorption model on the SiC side of the heterostructure.

[0123] Nb 2 CO 2 / Nb 1-x A x CO 2 C atom T on one side C 、O atom T O 、Nb / A atom T Nb / T A The top of the Nb-Nb-C atom T Nb-Nb-C and the bridge position B of the Nb-O / AC bond Nb-O / B A-C Adding Na atoms at a distance of 2 Å above gives Na in SiC / Nb 1- x A x CO 2 Heterostructure Nb 2 CO 2 / Nb 1-x A x CO 2 Adsorption model on one side.

[0124] For the interlayer C atom T C、O atom T O 、Nb / A atom T Nb / T A The top of the Nb-Nb-C atom T Nb-Nb-C and the bridge position B of the Nb-O / AC bond Nb-O / B A-C Adding Na atoms at a distance of 2 Å above gives Na in SiC / Nb 1-x A x CO 2 Adsorption model between heterostructure layers.

[0125] Adsorption energy calculation: The adsorption configurations at different sites constructed in the above steps were structurally optimized to obtain the energy-minimized adsorption configurations, and the adsorption configurations at different sites were calculated. E ad and the vertical distance H from the Na atom to the substrate. The results are shown in Table 2. The adsorption energy formula can be expressed as:

[0126] ; in, Sodium-doped SiC / Nb 1-x A x CO 2 The total energy of the heterojunction, is the total energy of the heterostructure without adsorbed Na atoms, is the total energy of a single Na atom in the bulk phase.

[0127] It can be clearly seen from Table 2 that the adsorption energies of all stable adsorption configurations of Na atoms are negative, indicating that Na atoms are stably adsorbed at all sites. 1-x A x CO 2 The adsorption energy of the top carbon atom on one side of the heterostructure SiC is higher than that on the pure SiC / Nb 2 CO 2 The adsorption energies in the heterostructures are more negative, indicating that Na atoms prefer to occupy these sites.

[0128] Table 2 Adsorption energy of stable adsorption configuration of Na atoms and vertical distance to the substrate Electronic property calculations By comparing and screening out the configuration with the lowest formation energy for each heterostructure, the electronic band structure, state density, differential charge density and Mulliken population analysis of relevant electronic properties are calculated at this time, such as Figure 8~Figure 15 According to the electronic band structure and state density before and after Na adsorption, it can be seen that the Na-treated SiC / Nb 1-x Ax CO 2 The metallic nature of the heterostructure is beneficial to improving the conductivity of the electrode. The differential charge density of the Na adsorbed heterostructure is as follows: Fig.16 As shown in the figure, a large amount of electrons gather on the SiC side, while electrons are lost around the Na atoms, indicating the transfer of electrons from the Na atoms to the substrate. At the same time, the formation of electron density between the Na atoms and the substrate indicates that the strong chemical interaction between the Na atoms and the substrate dominates. Mulliken population analysis further illustrates the above results. 1-x A x CO 2 The heterostructures shifted by 0.809 e, 0.862 e, 0.839 e, and 0.867 e, respectively.

[0129] The above-mentioned geometry optimization and performance calculation are implemented in the CASTEP module based on first principles, and the exchange-correlation functional is described by GGA-PBE generalized gradient.

[0130] For structure optimization and electronic property calculations, the plane wave cutoff energy was set to 450 eV, and a 4 × 4 × 1 K-point grid was used for Brillouin zone integration. In all calculations, the atoms were fully relaxed, and the force and energy convergence criteria were set to 0.01 eV Å, respectively. -1 and 1×10 -5 eV.

[0131] In the adsorption diffusion and capacity calculation process, the DFT-D3 method with Grimme correction was used to describe the long-range van der Waals interaction. In order to effectively avoid interlayer interaction, a vacuum layer greater than 15 Å was set along the z direction.

[0132] In the present invention, the Nosé-Hoover method is used to control the temperature and perform ab initio molecular dynamics simulations under the conditions of NVT ensemble, with the temperature set to 300K, the simulation duration to 3000 fs, and the time step to 1 fs.

[0133] Study on the Diffusion Kinetics of Na Atoms in Heterostructure Layers Diffusion path settings The most stable, second most stable and adjacent most stable adsorption configurations were used as the initial state, intermediate state and final state, respectively, and the possible sodium diffusion paths were set using MS software. 0.75 Ge 0.25 CO 2 For example, on the SiC side, the most stable site and the adjacent most stable T C The sites are the initial state and the final state, with T Si and T C(SiC) For the intermediate state, set three paths: TC -T C , T C -T Si -T C and T C -T C(SiC) -T C For Nb 75 Ge 25 CO 2 One side, set to T C -T C , T C -T O -T C and T C- T Nb -T C ; For the layers, the three paths are T C -T C , T C -T Nb -T C and T C -T Ge -T C ,like Fig.16 shown.

[0134] Transition state search The climbing elastic band method, namely CI-NEB, is used to search for transition states to achieve the selection of the optimal migration path, further obtain the diffusion barriers and diffusion coefficients of sodium atoms along different paths, and clarify the influence mechanism of alloying elements on diffusion dynamics.

[0135] In summary, compared with SiC / Nb 2 CO 2 In comparison, the SiC / Nb 1-x A x CO 2 The heterostructure model shows improved stability: since the alloying elements Ge and Sn have similar electronegativity to C, the bond strength of Sn-C / Ge-C is stronger than that of Nb-C, thus giving SiC / Nb 1-x A x CO 2 Good structural stability. The electron localization function calculation analysis shows that there is obvious electron density between the Ge-C and Sn-C bonds, indicating that they interact with each other through covalent bonds. Based on AIMD simulation, after 3000 fs complete relaxation at room temperature, the SiC / Nb constructed in Examples 1 to 4 of the present invention 1-x A x CO 2 The heterostructure model has only slight changes and small energy fluctuations, which fully confirms that the heterostructure model constructed by the present invention is thermodynamically stable.

[0136] Through the analysis of electron energy band and state density, compared with intrinsic SiC / Nb 2 CO 2 The heterostructure significantly increases the electronic state at the Fermi level by introducing alloy elements. The heterostructure exhibits significantly improved conductivity, and the metallic properties are maintained as Na atoms are continuously embedded in the heterostructure.

[0137] Adsorption energy calculations show that due to the synergistic effect between the two monolayers SiC / Nb 1-x A x CO 2 Compared with intrinsic SiC / Nb 2 CO 2 Compared with the original heterostructure, the heterostructure has a higher Na atomic adsorption strength. Thanks to the excellent theoretical capacity of the alloy elements Ge and Sn and the smaller molar mass, the heterostructure has a significantly improved Na storage capacity than the original heterostructure. In addition, the SiC / Nb 1-x A x CO 2 The interlayers show a reduced diffusion barrier, which is more conducive to the embedding and rapid migration rate of sodium atoms, and can achieve a fast charge and discharge rate.

[0138] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for constructing a heterostructure of a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: Constructing bulk Nb2C and SiC structural models, optimizing the bulk Nb2C and SiC structural models, and then constructing a 2DNb2CO2 unit cell model and a SiC unit cell model; constructing a single-layer Nb2CO2 super cell model and a single-layer SiC super cell model based on the Nb2CO2 unit cell model and the SiC unit cell model; The alloy element A is introduced into the single-layer Nb2CO2 supercell model to obtain Nb 1-x A x CO2 model; In the Nb 1-x A x A single layer of SiC supercell is placed on top of the CO2 model. After structural optimization, the SiC / Nb 1-x A x CO2 heterogeneous structure model; The alloy element A is Ge or Sn, and X is 0.15-0.

75.

2. The construction method according to claim 1, characterized in that: When the alloy element A is Ge and X is 0.25, the SiC / Nb 1-x A x CO2 heterostructure model is SiC / Nb 0.75 Ge 0.25 CO2, the lattice parameter is 6.31Å; when the alloy element A is Ge and X is 0.50, the SiC / Nb 1-x A x CO2 heterostructure model is SiC / Nb 0.50 Ge 0.50 CO2, lattice parameter is 6.15Å.

3. The construction method according to claim 1, characterized in that: When the alloy element A is Sn and X is 0.25, the SiC / Nb 1-x A x CO2 heterostructure model is SiC / Nb 0.75 Sn 0.25 CO2, the lattice parameter is 6.46Å; when the alloy element A is Sn and X is 0.50, the SiC / Nb 1-x A x CO2 heterostructure model is SiC / Nb 0.50 Sn 0.50 CO2, lattice parameter is 6.35Å.

4. A heterostructure of a sodium ion battery negative electrode material constructed by the construction method according to any one of claims 1 to 3.

5. A method for predicting the performance of a heterogeneous structure of a negative electrode material for a sodium ion battery according to claim 4, characterized in that: The performance prediction includes energy stability prediction, thermodynamic stability prediction, sodium ion adsorption stability prediction on heterostructure and conductivity prediction; The performance prediction method comprises the following steps: For the SiC / Nb 1-x A x The CO2 heterogeneous structure model was simulated by ab initio molecular dynamics to obtain the energy-time curve; the SiC / Nb 1-x A x The formation energy and phonon spectrum of the CO2 heterostructure model, energy stability prediction based on the energy-time variation curve, and thermodynamic stability prediction based on the formation energy and phonon spectrum; In the SiC / Nb 1-x A x In the CO2 heterostructure, SiC side and Nb 1-x A x CO2 side and the SiC / Nb 1-x A x Na atoms were added to different typical sites between the layers of the CO2 heterostructure to obtain the sodium atom adsorption model; The adsorption energy of sodium atoms on the surface of negative electrode materials is calculated based on the sodium atom adsorption model, and the adsorption stability of sodium ions on heterogeneous structures is predicted; By calculating SiC / Nb 1-x A x Electronic properties of CO2 heterostructures before and after sodium ion adsorption and the effect of sodium ions on the SiC / Nb 1-x A x The adsorption behavior, diffusion kinetics, open circuit voltage and theoretical specific capacity of CO2 on heterostructures are used to predict conductivity.

6. The method for predicting the performance of heterostructured negative electrode materials for sodium ion batteries according to claim 5, characterized in that: The method for constructing the sodium atom adsorption model is specifically as follows: Select the C atom on one side of SiC, the Si atom, the top of the C atom in SiC, and the Na atom 2Å above the Si-C bond bridge to obtain the Na in SiC / Nb 1-x A x Adsorption model of CO2 on the SiC side of heterostructure; Select Nb 1-x A x Na atoms were added to the C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and 2Å above the bridge of Nb-O / AC bonds on the CO2 side to obtain Na 1-x A x CO2 heterostructure Nb 1-x A x Adsorption model on the CO2 side; Select interlayer C atoms, O atoms, the top of Nb / A atoms, the top of Nb-Nb-C atoms, and add Na atoms 2Å above the bridge of Nb-O / AC bonds to obtain Na atoms in SiC / Nb 1-x A x Adsorption model of CO2 between heterogeneous structures.

7. The performance prediction method of the heterostructure of the negative electrode material of a sodium ion battery according to claim 5, characterized in that: The calculations were performed based on first principles using the CASTEP module, and the exchange-correlation functional was described using the GGA-PBE generalized gradient method.

8. The method for predicting the performance of heterogeneous structures of negative electrode materials for sodium ion batteries according to claim 5, characterized in that: When calculating the electronic performance data, the plane wave cutoff energy was set to 450 eV, and a 4 × 4 × 1 K-point grid was used for Brillouin zone integration. During the calculation process, the atoms were fully relaxed, and the force and energy convergence criteria were set to 0.01 eVÅ, respectively. -1 and 1×10 -5 eV.

9. The method for predicting the performance of heterostructured negative electrode materials for sodium ion batteries according to claim 5, characterized in that: In the calculation of adsorption behavior, diffusion kinetics and theoretical specific capacity, the DFT-D3 method with Grimme correction was used to describe the long-range van der Waals interaction, and a vacuum layer larger than 15 Å was set along the z direction to avoid interlayer interactions.

10. The method for predicting the performance of heterogeneous structures of negative electrode materials for sodium ion batteries according to claim 5, characterized in that: When performing ab initio molecular dynamics simulations, the Nosé-Hoover method was used to control the temperature and NVT ensemble conditions. The temperature was set to 300 K, the simulation duration was 3000 fs, and the time step was 1 fs.

Citation Information

Patent Citations

  • Monoatomic dispersed MXene materials and applications in lithium battery negative electrodes

    CN111029531A

  • Aluminum-based composite material containing MAX phase reinforcing material and preparation method of aluminum-based composite material

    CN116334451A

  • Artificial synaptic device based on Nb2C-zinc oxide memristor and preparation method thereof

    CN118555906A

  • Preparation method and performance prediction method of heterostructure sodium ion battery negative electrode material

    CN118993049A

  • Preparation method of fluorescent colorimetric dual-mode sensor based on CRISPR / Cas12a integrated MXene composite material

    CN119165153A

Cited By

  • Design method of infinite layer nickel oxide with low sodium ion migration barrier

    CN119296692A

  • Heterostructure performance analysis method

    CN120636636A